Clinical relevance of single nucleotide polymorphisms in the CXCL1 and CXCL12 genes in patients with major trauma. - Wang, Xiao; Zhang, An-Qiang; Gu, Wei; Wen, Da-Lin; Lu, Hong-Xiang; Yang, Jian-Hua; Wang, Xu; Deng, Jin; Zhang, Hong-Qi; Du, Ding-Yuan; Zhang, Lian-Yang; Zeng, Ling; et al. (Journal of Trauma & Acute Care Surgery, 2019)
Background: Genetic backgrounds have been recognized as significant determinants of susceptibility to sepsis. CXC chemokines play a significant role in innate immunity against infectious diseases. Genetic polymorphisms of CXC chemokine genes have been widely studied in inflammatory and infectious diseases but not in sepsis. Thus, we aimed to investigate the clinical relevance of CXC chemokine gene polymorphisms and susceptibility to sepsis in a traumatically injured population.Methods: Thirteen tag single nucleotide polymorphisms were selected from CXC chemokine genes using a multimarker tagging algorithm in the Tagger software. Three independent cohorts of injured patients (n = 1700) were prospectively recruited. Selected single nucleotide polymorphisms were genotyped using an improved multiplex ligation detection reaction method. Cytokine production in lipopolysaccharide-stimulated whole blood was measured using an enzyme-linked immunosorbent assay.Results: Among the 13 tag single nucleotide polymorphisms, four single nucleotide polymorphisms (rs1429638, rs266087, rs2297630, and rs2839693) were significantly associated with the susceptibility to sepsis, and three (rs3117604, rs1429638, and rs4074) were significantly associated with an increased multiple organ dysfunction score in the derivation cohort. However, only the clinical relevance of rs1429638 and rs266087 was confirmed in the validation cohorts. In addition, rs2297630 was significantly associated with interleukin 6 production.Conclusion: The rs1429638 polymorphism in the CXCL1 gene and the rs2297630 polymorphism in the CXCL12 gene were associated with altered susceptibility to sepsis and might be used as important genetic markers to assess the risks of sepsis in trauma patients.Level Of Evidence: Prognostic and epidemiologic study, level II.